The Effect of Working Capital Management on Firm’s Performance of Food and Beverages Sector in Malaysia - Suzila, Mohamed Yusof; Nazaria, Md. Aris; Muhammad Hikmal, Ismail (UNIMAS Publisher, 2019)
This research examines the effect of working capital management (WCM) variables and firm’s performance using the data collected and analysed from listed firms in food and beverages sector on Bursa Malaysia. The sample comprises of 50 firms and the data is for 5 years from 2014 to 2018. The methodologies adopted in this research includes descriptive analysis, correlation analysis, Pooled Ordinary Least Square (OLS) regression, Breusch-Pagan (BP) Lagrange Multiplier test, and Hausman test. Various determinants of WCM have been identified to represent the independent variables (IV) namely days of accounts receivable, days of accounts payable, inventory turnover in days and cash conversion cycle. The dependent variable uses Return on Assets (ROA) as a proxy to measure the firm’s performance. In this study, these two variables, accounts payable and cash conversion cycle has a significant and positive effect towards firm’s performance of food and beverages sector in Malaysia.